Local limit theorem for triangular array of random variables - Korchinsky, I.A.; Kulik, A.M. (Інститут математики НАН України, 2007)
For a triangular array of random variables {Xk,n, k = 1, . . . , cn; n belongs N} such that, for every n, the variables X1,n, . . .,Xcn,n are independent and identically distributed, the local limit theorem for the variables Sn = X1,n + · · · + Xcn,n is established.